Harmonics distortions and interactions of modern residential electrical loads - M.Alawasa, Khaled (International Journal of Engineering and Technology, 2018)
Driven by continuous growth in electrical energy cost and technologies developments in power electronics performance, customers have been motivated towards utilization of power electronics loads and energy-efficient appliances at their houses. Power electronics devices are one of the main harmonics sources. With high proliferation of such devices in electrical system, it is imperative to examine the harmonics profile of such houses. The purpose of this paper is to investigate and characterize the harmonics distortion level on typical Jordanian modern residential loads. A field data survey for the harmonic distortions of the individual residential loads is presented. Synchronized measurements are conducted to point out the contribution of each individual loads to the net total harmonic distortion level (THD) and to explain harmonic interaction between the loads. The results show a high level of harmonics distortion in current, reaches as high as 45%.